Prevention of Foodborne Listeriosis - JM Farber; J Harwig; A Carter (Canadian Journal of Infectious Diseases)
Listeria monocytogenes is a Gram-positive, rod-shaped bacterium which, although recognized in the medical literature as an opportunistic pathogen for the past 60 years, has only recently gained prominence as an important foodborne pathogen. Factors which make this organism unique among foodborne pathogens include its ability both to survive in foods under a variety of adverse conditions and to grow at low refrigeration temperatures. The organism is very widespread in the environment and can be found in a wide variety of foods. At least four major outbreaks definitively linked to the consumption of food containing L monocytogenes have occurred. In addition there have been a number of recent sporadic cases of listeriosis linked to the consumption of meat, fish and dairy products. The primary concern of the Health Protection Branch is contaminated foods in which L monocytogenes can grow well, and which would not normally be heated prior to consumption. Worldwide, the disease appears to be increasing in incidence, but definite links to foods are difficult to make. In most cases, individuals who come down with listeriosis include the immunocompromised, the elderly (older than 65 years) and pregnant women and their fetuses. Primary manifestations of the disease include meningitis, spontaneous abortion and septicemia. Mortality rates in foodborne listeriosis outbreaks are approximately 30%. Diagnosis of listeriosis usually requires isolation of the organism from sterile sites such as blood, cerebrospinal fluid, placenta and meconium and gastric aspirates from neonates. The recommended drug of choice is high dose intravenous ampicillin. Advice to physicians concerning measures to prevent foodborne listeriosis in high risk groups is reviewed. Included among these recommendations is avoidance of consumption of potentially hazardous foods such as soft cheese and raw products of animal origin.